Growth and meat yield in native Naked Neck, exotic chicken and their crossbreds: F2 generation* - HAQUE, M E; HOWLIDER, M A R (The Indian Journal of Animal Sciences, 2013)
Growth perfonnance at different ages from day.old to 17 weeks were recorded on 392 chicks of different genotypes:Naked Neck desi (NaD), Rhode Island Red (RIR), White Leghorn (WL), Fayoumi (Fy) and their crosses (NaDRIR,NaDWL and NaDFy). Meat yield of these 7 genotypes were compared using 28 cockrels of 12 weeks of age. Amongcrossbreds highest day-old weight was in NaDRIR followed by NaDWL and NaDFy. Highest body weight gain and bestfeed conversion efficiency was in NaDRIR followed by NaDFy and NaDWL at 17 weeks of age. Highest breast meat wasproduced by NaD followed by NaDFy, NaDWL and NaDRIR. NaDFy was the best in total meat yield per cent among allgenotypes. Naked neck (Na) crossbrebs had better growth and meat yield than that of other genotypes. Superiority ofbreast meat seemed to be the main advantage ofNa crossbreds.